Ryanodine receptor-mediated Ca2+ release underlies iron-induced mitochondrial fission and stimulates mitochondrial Ca2+ uptake in primary hippocampal neurons - SanMartín, Carol D.; Paula-Lima, Andrea C.; García, Alejandra; Barattini, Pablo; Hartel, Steffen; Núñez, Marco T.; Hidalgo, Cecilia (Frontiers in Molecular Neuroscience, 2014)
Mounting evidence indicates that iron accumulation impairs brain function. We have reported previously that addition of sub-lethal concentrations of iron to primary hippocampal neurons produces Ca2+-signals and promotes cytoplasmic generation of reactive oxygen species. These Ca2+ signals, which emerge within seconds after iron addition, arise mostly from Ca2+ release through the redox-sensitive ryanodine receptor (RyR) channels present in the endoplasmic reticulum. We have reported also that addition of synaptotoxic amyloid-β oligomers to primary hippocampal neurons stimulates RyR-mediated Ca2+ release, generating long-lasting Ca2+ signals that activate Ca2+-sensitive cellular effectors and promote the disruption of the mitochondrial network. Here, we describe that 24 h incubation of primary hippocampal neurons with iron enhanced agonist-induced RyR-mediated Ca2+ release and promoted mitochondrial network fragmentation in 43% of neurons, a response significantly prevented by RyR inhibition and by the antioxidant agent N-acetyl-L-cysteine. Stimulation of RyR-mediated Ca2+ release by a RyR agonist promoted mitochondrial Ca2+ uptake in control neurons and in iron-treated neurons that displayed non-fragmented mitochondria, but not in neurons with fragmented mitochondria. Yet, the global cytoplasmic Ca2+ increase induced by the Ca2+ ionophore ionomycin prompted significant mitochondrial Ca2+ uptake in neurons with fragmented mitochondria, indicating that fragmentation did not prevent mitochondrial Ca2+ uptake but presumably decreased the functional coupling between RyR-mediated Ca2+ release and the mitochondrial Ca2+ uniporter. Taken together, our results indicate that stimulation of redox-sensitive RyR-mediated Ca2+-release by iron causes significant neuronal mitochondrial fragmentation, which presumably contributes to the impairment of neuronal function produced by iron accumulation.